Development of higher education in the European Union and Ukraine: trends educational policy - Mospan Natalia (Borys Grinchenko Kyiv Metropolitan University, 2015)
The article analyzes the impact of policies on the development of educational systems in the European Union and Ukraine. The sources are independent reports of the European Commission, and state documents on higher education in Ukraine. A detailed study of the European Commission reports helps to identify internal and external factors, which have different effects on higher education in the European Union. The external factors include global process of internationalization of higher education and its consequences. Under internal factors we concider the Lisbon strategy and the Bologna process. One could argue that education systems in the European Union will develop under the influence of external and internal factors, where the dominant position of the Lisbon Strategy and the Bologna process will win the lead role. Since the signing of the Bologna Convention in 2005, higher education in Ukraine has been in a state of current changes. Analysis of the new Higher Education Law of Ukraine made it possible to outline the major innovations in the reforms of higher education and similar policy trends of higher education in the European Union and Ukraine.